Modeling, optimization and AI-forecasting technology in Raman spectrometry - Bilak, Yu. (Проблеми керування та інформатики, 2025)
In the work, the technology of modeling, optimization and prediction of spectral characteristics of thin films based on Raman spectroscopy with the use of artificial intelligence was developed. Modern machine learning methods are implemented, including ensemble algorithms (random forest, gradient boosting) and neural networks, which ensures high accuracy of forecasts and automation of spectrum analysis. An innovative approach includes the use of the Voight profile, which combines Lorentzian and Gaussian components, allowing to describe accurately the width and shape of the peaks for approximation, taking into account the physicochemical parameters of the films and the influence of experimental conditions. У роботі описано розробку технології моделювання, оптимізації та прогнозування спектральних характеристик тонких плівок на основі раманівської спектроскопії із застосуванням штучного інтелекту. Розглянуто впровадження сучасних методів машинного навчання, включно з ансамблевими алгоритмами (випадковий ліс, градієнтний бустинг) та нейронними мережами, що забезпечує високу точність прогнозів і автоматизацію аналізу спектрів. Інноваційний підхід передбачає використання профілю Войта, який поєднує лоренцівську та гаусівську складові, що дає змогу точно описувати ширину і форму піків для апроксимації з урахуванням фізико-хімічних параметрів плівок і впливу експериментальних умов.